Pattern of Character Building for Students in Middle School and Islamic Boarding Schools - A. Aco Agus; Sukri Badaruddin; Musria Muh. Nur (Jurnal Ad'ministrare, 2020)
This study aims to describe the pattern of character formation of students in Schools and Islamic Boarding Schools (studies on MTs Ma'Had Hadith Al-Junadiyah Biru with Watampone 3 Middle School. The subjects in this study are the Principal of Watampone 3 Middle School, Principal of Madrasah Tsanawiah Ma'Had Al-Junadiyah Blue Hadith, Religious Teachers, PPKn Teachers, Social Studies Teachers from Both Educational Institutions studied and students and students.The data collection was used by means of observation, interviews, documentation.The research instruments were supported through interview guidelines, observation guidelines and documentation documentation. The research shows that the two educational units, among others, namely SMP Negeri 3 Watampone and Madrasah Tsanawiah Ma'Had Al-Junadiyah Blue have similar character formation patterns in terms of methods while in terms of strategy formation patterns are carried out with different approaches. Watampone in terms of the method emphasizes more on the teacher's approach to the students in shaping the character of students, besides the emphasis on the integration of character education in certain subjects. In terms of strategy, SMP Negeri 3 Watampone emphasizes more on the pattern of character formation through extracurricular activities where through extracurricular activities there are 3 expected patterns of character formation, they are habituation, exemplary, and culture. while the Madrasah Tsanawiah Ma'Had Hadith Al-Junadiyah Biru strategy applied in the pattern of character education through the activity of apples every morning before entering the class to practice the discipline of students.